2019
DOI: 10.1097/iae.0000000000002591
|View full text |Cite
|
Sign up to set email alerts
|

Internal Limiting Membrane Peeling Versus Nonpeeling to Prevent Epiretinal Membrane Development in Primary Rhegmatogenous Retinal Detachment

Abstract: Purpose: To determine whether internal limiting membrane peeling in primary rhegmatogenous retinal detachment prevents epiretinal membrane (ERM) development. Secondarily, we propose a classification system for postoperative ERMs. Methods: Retrospective, interventional, comparative case series. Consecutive eyes with primary rhegmatogenous retinal detachment (n = 140) treated by a single surgeon. The presence of postoperative ERMs was assessed with swept-source optical coherence tomography. Results: An ERM was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…Because this was a multicenter study, it was almost impossible to obtain follow-up data for a longer period than that used for data collection for the Registry. However, the follow-up period was also at least 6 months after the initial vitrectomy in other reports [ 3 , 27 ]. Those reports did not include follow-up for a full 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Because this was a multicenter study, it was almost impossible to obtain follow-up data for a longer period than that used for data collection for the Registry. However, the follow-up period was also at least 6 months after the initial vitrectomy in other reports [ 3 , 27 ]. Those reports did not include follow-up for a full 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a range of risk factors associated with the formation of ERM after RRD repair, including age (4) , equatorial breaks (8) , cryopexy (9) , repeated operations (10) , proliferative vitreoretinopathy (11) , macular involvement (3) , low preoperative visual acuity (12) , and multiple and/or large retinal breaks (4) . Our study recorded that horseshoe breaks and giant retinal tears were significantly associated with the ERM development.…”
Section: Discussionmentioning
confidence: 99%
“…ILM peeling leads to mechanical trauma in the retinal microstructures, which can result in the dimple sign, pitting, temporal macular thinning, and concentric macular dark spots ( Figure 3(a) ) [ 6 ]. However, the effect of this anatomical damage on visual function remains controversial [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the statistical analysis, VA in decimal fraction was transformed to the logarithm of the minimum angle of resolution (logMAR). Low VA states were recorded as follows: counting fingers (logMAR = 1.7), hand motion (logMAR = 1.8), light perception (logMAR = 1.9), and no light perception (logMAR = 2.0) [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation